Reasons for refraining from criminal activity - Veneziano, Carol (American journal of criminal justice, 1995)
In order to establish the relative importance of reasons for not engaging in illegal activities, respondents were administered a questionnaire containing a list of possible factors that could account for not committing crimes, and were then asked to rank them. Multidimensional scaling analyses revealed the underlying structure of these factors. Specifically, respondents tended to structure their reasons based on the formality/informality of a negative consequence and the relative seriousness of a sanction.